AGE AND GROWTH OF THE LESSEPSIAN MIGRANT LAGOCEPHALUS SPADICEUS (ACTINOPTERYGII: TETRAODONTIFORMES: TETRAODONTIDAE) FROM THE GULF OF ISKENDERUN, NORTH-EASTERN MEDITERRANEAN, TURKEY - Basusta, Asiye; Basusta, Nuri; Ozcan, Ebru Ifakat; Girgin, Hulya (Wydawnictwo Akad Rolniczej W Szczecinie, 2020)
Background. The population of Lagocephalus spadiceus (Richardson, 1845), one of the Lessepsian species that migrated from the Red Sea to the Mediterranean Sea through the Suez Canal, has been growing rapidly in Turkey in recent years. This situation poses a serious danger to fisheries and human health. There is little information about the biology of this species. The presently reported study permits a greater understanding of the age and growth characteristics of the pufferfish L. spadiceus from the Gulf of Iskenderun, north-eastern Mediterranean. Materials and methods. Samples were captured by commercial bottom trawlers at depths of 24-50 m during 9 trawling operations conducted during the fishing seasons between 2012 and 2013 in the Gulf of Iskenderun, north-eastern Mediterranean. Age determinations were carried out using vertebrae. Images of vertebrae suitable for age determination were obtained with a dissecting microscope. The index of the mean percentage error (IMPE) was calculated to assess the precision of the age determinations between two independent readers. Growth parameters for all individuals were then determined by fitting observed and length-at-age data using the von Bertalanffy growth equation. In addition, the condition factor (CF) was determined. Results. A total of 1116 specimens (529 females and 587 males) were sampled, ranging from 6.7 to 34.0 cm in total length and from 4.30 to 557.64 g in weight. The female-to-male ratio was 1:1.1. Age determination was conducted using vertebral band counts. The age of the examined specimens ranged from 0 to 10 years. One female individual was determined to be 17 years of age (45.6 cm and 1269.0 g). The von Bertalanffy growth equations were Lt = 47.21[1 - e(-0.116(t + 2.04))] and Wt = 1296.18 [1 - e(-0.116(t + 2.04))](2.846) for females, L-t = 46.36 [1 - e(-0.133(t + 1.76))] and Wt = 1381.86 [1 - e(-0.133(t + 1.76))]2.817 for males and L-t = 46.90 [1 - e(-0.120(t + 1.97))] and W-t = 1345.67 [1 - e-(0.120(t + 1.97))](2.831) for all individuals. The growth performance index (Phi ') value was calculated as 2.421 for all individuals. The condition factor ranged from 0.890 to 2.768 for females and from 0.899 to 2.767 for males. Conclusions. It is very important to investigate L. spadiceus, an invasive species, in order to prevent its harmful effects on fisheries and human health. As this study is the first study on the age and growth of L. spadiceus in the northeastern Mediterranean, it will significantly contribute to future ecosystem conservation and management strategies.
Keywords: half-smooth golden pufferfish; growth parameters; vertebrae; condition factor; north-eastern Mediterranean